Volumes of random 3-manifolds - Viaggi, Gabriele (Journal of topology, 2021)
We prove a law of large numbers for the volumes of families of random hyperbolic mapping tori and Heegaard splittings providing a sharp answer to a conjecture of Dunfield and Thurston.